Leila Chen ([Kingston, Jamaica] : Planters' Punch, 1930)
Miss Leila Chen, who is secretary to Messrs. Wood, Carman and Costa, [1930]
Keywords: Chen, Leila; Chinese - Jamaica - History; Chinese - Jamaica